2010
DOI: 10.1007/s12011-010-8908-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Phosphorus Content of the Sino-atrial Nodes and Other Cardiac Regions of Monkeys

Abstract: To examine whether there were gender differences in the sino-atrial node (SAN), the authors investigated the gender difference in the SAN using monkey hearts by direct chemical analysis from a viewpoint of element contents. The used rhesus and Japanese monkeys consisted of 30 males (average age=6.5±7.5 years) and 30 females (average age=12.2±10.3 years), ranging in age from newborn to 30 years. The SAN tissues were removed from the anatomical position of monkey hearts and were confirmed by means of histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…As for the tissues of monkeys, the authors investigated age-related changes of elements in the coronary arteries [1], cardiac valves [2], cardiac walls [3], sinoatrial node [4,5], and peroneus longus tendon [6] and found that in all of the four cardiac valves, cardiac walls of the left and right atria and ventricles, and sinoatrial node, the P content decreased significantly in childhood. With regard to the coronary arteries, the P content did not change significantly in the left and right coronary arteries with aging.…”
Section: Introductionmentioning
confidence: 99%
“…As for the tissues of monkeys, the authors investigated age-related changes of elements in the coronary arteries [1], cardiac valves [2], cardiac walls [3], sinoatrial node [4,5], and peroneus longus tendon [6] and found that in all of the four cardiac valves, cardiac walls of the left and right atria and ventricles, and sinoatrial node, the P content decreased significantly in childhood. With regard to the coronary arteries, the P content did not change significantly in the left and right coronary arteries with aging.…”
Section: Introductionmentioning
confidence: 99%